Incidence of heavy metals in the mangrove flora and sediments in Kerala, India - George Thomas & Tresa V. Fernandez (Hydrobiologia 352: 77-87, 1997., 1997)
The mangroves of Kerala on the south-west coast of India are fast disappearing due to land reclamation and other anthropogenic disturbances. There are very few ecosystem level studies made in these much threatened biotopes in Kerala. The present study involves the measurement of heavy metals in the mangrove flora and sediments of three mangrove habitats along the Kerala coast. Sampling was carried out for a period of one year at bi-monthly intervals, with concentrations of Fe, Mn, Cu, Zn, Pb and Co analysed using atomic absorption spectrophotometry. An appreciable variation was observed in metal concentrations in different mangrove species. Cu, Zn and Pb were found to be in higher concentrations in Avicennia officinalis whereas higher levels of Fe, Mn and Co were observed in the species Barringtonia racemosa. The analysis of heavy metals indicated a high level of metal pollutants such as Fe, Cu, Zn and Pb in the mangrove habitats of Quilon and Veli compared to the relatively uncontaminated areas of Kumarakom.